2015
DOI: 10.1371/journal.pone.0144048
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance and Physical Activity in Older Adults: Associated but Separate Domains of Physical Function in Old Age

Abstract: BackgroundPhysical function is a crucial factor in the prevention and treatment of health conditions in older adults and is usually measured objectively with physical performance tests and/or physical activity monitoring.ObjectiveTo examine whether 1) physical performance (PP) and physical activity (PA) constitute separate domains of physical function; 2) differentiation of PA classes is more informative than overall PA.DesignCross-sectional study to explore the relationships within and among PP and PA measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 36 publications
8
109
0
1
Order By: Relevance
“…The lack of association between volumes of activity and physical performance measures concurs with earlier reports (van Lummel et al, 2015;Weiss et al, 2013). Others have found associations between laboratory-based gait speed measures (Giannouli et al, 2016;Hall et al, 2017) (which we did not measure) and step count, although comparisons are limited due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of association between volumes of activity and physical performance measures concurs with earlier reports (van Lummel et al, 2015;Weiss et al, 2013). Others have found associations between laboratory-based gait speed measures (Giannouli et al, 2016;Hall et al, 2017) (which we did not measure) and step count, although comparisons are limited due to methodological differences.…”
Section: Discussionsupporting
confidence: 92%
“…Step and Dynamic Gait Index) for those aged 70 -80+ (van Lummel et al, 2015;Weiss et al, 2013). Stronger associations were reported for selected micro gait characteristics and physical performance measures in a study comparing physical activity in fallers and non-fallers (Weiss et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Physical performance is a multidimensional concept, including several subdomains: muscle strength, mobility (lower extremity function), dexterity (upper extremity function), axial ability (neck and back function), and ability to carry out instrumental activities of daily living. 8 Some cross-sectional studies showed a significant relationship between low physical performance and depression. 9,10 However, there is a lack of clarity about these results, due to the cross sectional nature and the directionality of the association, since depression is characterized by fatigue and asthenia, which may themselves lead to a decrease in activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among others (see below), a particular downside of when PD patients visit doctors in professional environments is that this does not provide an accurate assessment of patient physical activity. Office‐based tests preferentially assess physical performance, which is closer to a stress test than to physical activity, and it has recently been shown that an assessment of physical performance does not automatically allow one to draw conclusions about physical activity status, that is, a valid evaluation of (the activity level of) patient lifestyle . Therefore, complementary assessment strategies are needed.…”
Section: Which Pd Features Should Be Prioritized In the Development Omentioning
confidence: 99%